A cosmeceutical formulation based on boswellic acids for the treatment of erythematous eczema and psoriasis - Togni S; Maramaldi G; Di Pierro F; Biondi M (Dove Medical Press, 2014)
Stefano Togni,1 Giada Maramaldi,1 Francesco Di Pierro,2 Massimo Biondi3 1Indena S.p.A., Milan, Italy; 2Velleja Research, Milan, Italy; 3Dermatology Unit, ASL Piacenza, Piacenza, Italy Background: Boswellic acids (BAs) show anti-inflammatory properties in a variety of inflammatory diseases, including rheumatoid arthritis, osteoarthritis, and asthma. A topical administration route is currently used to deliver active compounds in psoriatic and eczematous patients. In this double-blind study we compare a novel BA formulation (containing Bosexil®, INCI [International Nomenclature of Cosmetic Ingredients]: lecithin, Boswellia serrata resin extract) with a placebo formulation. A third arm of the trial received a formulation of Vaccinium myrtillus seed oil, previously demonstrated as an effective local treatment for psoriatic lesions. Methods: Patients with psoriasis or erythematous eczema were randomly assigned, in a 1:1:1 ratio, to Bosexil®, V. myrtillus seed oil, or placebo. In order to evaluate the effects of treatment, the changes of scales and erythema from diagnosis to the end of treatment were scored in psoriatic patients, while changes in itch and erythema were analyzed for erythematous eczema patients. Psoriasis Area Severity Index and Eczema Area and Severity Index scores were also calculated. Results: In patients with psoriasis, scales and erythema improved both with Bosexil® and the V. myrtillus seed oil treatment in comparison with placebo. In particular, the treatment with Bosexil® formulation improved scales (70% of cases) and erythema (50% of cases) without any case of worsening. In patients with eczema, the administration of placebo did not result in any improvement in 90% of cases, and in the remaining 10% worsened both itch and erythema. Bosexil® formulation improved both itch (60% of cases) and erythema (60% of cases) without any case of worsening. V. myrtillus seed oil improved itch and erythema in 66.7% and 77.8% of patients, respectively. Conclusion: A topical formulation of Bosexil® may be promising for the treatment of psoriasis and erythematous eczema. Long-term studies are recommended to evaluate the adherence to this topical treatment and its clinical benefits in real life. Keywords: boswellic acids, cosmeceutical, inflammation, psoriasis, erythematous eczema